An Analysis on Translation Techniques in The Subtitle of The Movie “Avatar” - Ananta, I Made Wiprah (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2023)
Abstract: This study investigated the intricate process of translating thoughts and ideas between different languages, which goes beyond mere linguistic proficiency. Successful translation requires a deep comprehension of cultural nuances in both the source and target languages, as well as a thorough understanding of the text and the intended audience. The aim is to achieve accurate and effective translations while avoiding literal interpretations, potential misunderstandings, and inaccuracies. The focus of this study is the specific translation techniques employed in subtitling the renowned film "Avatar." To conduct this research, a qualitative approach using descriptive methods is adopted, utilizing dialogue and subtitles from the movie as the primary data source. The analysis involves the identification of translation techniques based on Newmark's framework (1988) and references Larson's classification of translation types (1945). Through this study, a comprehensive exploration of the diverse translation techniques used in subtitling "Avatar" is undertaken. The findings emphasize the significance of cultural knowledge in achieving successful translations. It is encouraged that future research delves into other films to gain a broader understanding of subtitle translation, encompassing various translation methods, procedures, and other pertinent aspects of translation.